The correlation of crude corrosivity in different field service environments with hydrogen flux measurements - Serate, Duane Go.
This study provides the theoretical analysis and field results of a prototype real-time portable hydrogen collector method, called Hydrosteel. This instrument detects and measures the hydrogen diffusion through steel, as a result of napthenic acid corrosion (NAC) from high Total Acid Number (TAN) crudes
Fe+2RCOOH 2RCOOH Fe (RCOO)2 + H2
High TAN crudes (TAN>1) are identified with high potential margins but are considered high risk of causing NAC during refinery processing. Five corrosion loops were studied in the Crude Distilling Unit (CDU). The hydrogen flux results were correlated with the crude oil characteristics, process conditions, and with another corrosion mechanism called Sulphidation that occurs simultaneously at the same process conditions
Fe(s) + H2S(g) FeS(s)+H2(g)
The Hydrosteel portable hydrogen collection method was able to demonstrate that high flux readings could be obtained on a system that is expected to be corrosive and demonstrated that high hydrogen permeation readings could indeed be detected and correlated to the prevailing process conditions. Good correlation was achieved for the hydrogen activity with the total acid number (TAN), crude existing sulfur content, crude fraction sulfur content, crude existing and potential H2S, % yield of the crude and the CDU throughput. The work was able to shortlist the corrosion hotspots for NAC-sulphidation in the crude distiller unit, from five corrosion loops known theoretically to have NAC-sulphidation, down to two corrosion loops: the Transfer Line and the Heavy Gasoil (HGO) Stream. This is consistent with the other studies pointing to these areas as the locations where NAC is most active.
Thesis (MS Materials Science and Engineering)--University of the Philippines Diliman.